In vitro evaluation of antioxidant properties of Chlorella vulgaris and its derivatives for use as antioxidant supplements in animal production - SIKIRU, A B; ARANGASAMY, A; ALEMEDE, I C; EGENA, S S A; BHATTA, R; RAO, S B N (The Indian Journal of Animal Sciences, 2024)
Bioactive compounds with varied functional properties found in microalgae such as Chlorella vulgaris can serve as antioxidants supplement against free radicals causing oxidative stress in food animals, but there is a need to quantify these antioxidants in the algae for effective applications. Therefore, this study quantified antioxidants in Chlorella vulgaris and derivatives prepared with the microalgae biomass for enhancing its application in animal nutrition. Eight derivatives prepared using the Chlorella vulgaris biomass were subjected to in vitro antioxidant supplements in animals for attenuation of oxidative stress to improve performances and productivity because of their antioxidant potentials. Antioxidant assessments including ferric antioxidant power, hydrogen peroxide scavenging potential, total antioxidant capacity, and total phenolic content. The results showed that the mean total capacities of the preparations were 621.83±36.41 µmol/g ascorbic acid equivalent, ferric reducing antioxidant power (FRAP) was 1.28±0.09, while the hydrogen peroxide scavenging (HPS) potential was 34.04±3.18%, and the total phenolic content was 30.54 mg/g ellagic acid equivalent. It was concluded from these observations that the microalgae Chlorella vulgaris and its derivatives as prepared in this study could be used as antioxidant supplements in animals for attenuation of oxidative stress to improve performances and productivity because of their antioxidant potentials.